Sex-specific effects of TLR9 promoter variants on spontaneous clearance of HCV infection. Issue 10 (21st April 2016) - Fischer, Janett; Weber, Alexander N R; Böhm, Stephan; Dickhöfer, Sabine; El Maadidi, Souhayla; Deichsel, Danilo; Knop, Viola; Klinker, Hartwig; Möller, Bernd; Rasenack, Jens; Wang, Lisa; Sharma, Manu; et al.
Abstract : Objective: As pathogen sensors, Toll-like receptors (TLR) play a role in the first defence line during HCV infection. However, the impact of the DNA sensor TLR9 on the natural course of HCV infection is unknown. To address this, TLR9 promoter polymorphisms (single nucleotide polymorphisms (SNPs)) rs187084 and rs5743836 were investigated for their effect on disease progression. Design: Therefore, the TLR9 SNPs and the interferon lambda 4 ( IFNL4 ) rs12979860 were genotyped in chronically HCV type 1 infected (n=333), in patients who spontaneously cleared the infection (n=161), in the Swiss HCV cohort (n=1057) and the well-characterised German (n=305) and Irish (n=198) 'anti-D' cohorts. Functional analyses were done with promoter reporter constructs of human TLR9 in B cells and assessing TLR9 mRNA levels in whole blood of healthy volunteers. Results: The TLR9 rs187084 C allele was associated with spontaneous virus clearance in women of the study cohort (OR=2.15 (95% CI 1.18 to 3.90) p=0.012), of the Swiss HCV cohort (OR=2.06 (95% CI 1.02 to 4.18) p=0.044) and in both 'anti-D' cohorts (German: OR=2.01 (95% CI 1.14 to 3.55) p=0.016; Irish: OR=1.93 (95% CI 1.10 to 3.68) p=0.047). Multivariate analysis in the combined study and Swiss HCV cohorts supported the results (OR=1.99 (95% CI 1.30 to 3.05) p=0.002). Functional analyses revealed higher transcriptional activities for both TLR9 variants and an association of the C allele of rs5743836 with allele-specific TLR9 mRNA regulation by oestrogens in women. Conclusions: TLR9 promoter SNPs are associated with the natural course of HCV infection and show higher transcriptional activities. Our results imply the DNA sensor TLR9 in natural immunity against the RNA virus, HCV.